The biology of thought : a neuronal mechanism in the generation of thought - a new molecular model - Dharani, Krishnagopal (AP, 2015)
The question of ""what is thought"" has intrigued society for ages, yet it is still a puzzle how the human brain can produce a myriad of thoughts and can store seemingly endless memories. All we know is that sensations received from the outside world imprint some sort of molecular signatures in neurons - or perhaps synapses - for future retrieval. What are these molecular signatures, and how are they made? How are thoughts generated and stored in neurons? The Biology of Thought explores these issues and proposes a new molecular model that sheds light on the basis of human thought. Step-by-ste.